Prenatal echocardiographic diagnosis of a discontinuous left pulmonary artery with Taussig–Bing syndrome: a case report and literature review - He, Yun; Yang, Yufei; Song, Xiaoyu; Zhang, Zhonglei; Yan, Dingfang; Xie, Chao; Zeng, Min; Zhang, Wenjun (Frontiers in Pediatrics, 2024)
Background: Unilateral pulmonary artery discontinuity (UPAD) is a rare foetal abnormality, for which prenatal ultrasonographic diagnosis remains challenging. We report a case of left pulmonary artery discontinuity in association with Taussig-Bing syndrome, which has rarely been reported in literature so far.Case presentation: A pregnant woman with CHD at 23 weeks gestation was referred to our center. She denied any familial history of genetic disorders in both spouses and Noninvasive prenatal testing (NIPT) also showed low risk. An ultrasound examination revealed a complex cardiac malformation indicative of left pulmonary artery originating from the ductus arteriosus with Taussig-Bing syndrome. The family eventually chose to terminate a pregnancy and agreed to an autopsy, which confirmed that prenatal echocardiographic diagnosis was correct. In addition, we reviewed and analyzed 17 reported cases of prenatal echocardiographic diagnosis of UPAD.Conclusions: UPAD is characterized by discontinuity between the proximal and distal pulmonary arteries, along with a ductal origin of distal pulmonary artery. Discontinuous pulmonary artery originating from the ductus can be detected on prenatal sonography using ultrasound technology. The aim is to detect malformations earlier and carry out necessary intervention measures as soon as possible.